Prognostic assessment and management of a patient with Carmi syndrome. A case report. (July 2021) - Schreiner, D.; Uebler, A.; Ginghina, C.; Muensterer, O.; Has, C.; Mildenberger, E.
Abstract: Carmi syndrome is a rare and severe disease defined by pyloric atresia and junctional epidermolysis bullosa. There are no clear recommendations when to consider a curative therapy, including surgical repair of pyloric atresia and when to transition to palliative care. We report the case of a female preterm infant suffering from Carmi syndrome. After definitive diagnosis and appropriate ethical counselling, we decided for surgical repair of the pyloric atresia. Nonetheless, there was no clinical improvement and our patient died after 35 days. Reviewing the literature, we found immunofluorescence microscopy to be most decisive examination to determine the prognosis of this severe disease. Highlights: Carmi syndrome (JEP-PA) is a rare and severe disease defined by pyloric atresia and junctional epidermolysis bullosa. The overall mortality is reported to be 75%. Decisive for prognosis is the quantity of integrin evaluated by immunofluorescence microscopy. Decision about curative therapy or a palliative approach should be made in an interdisciplinary clinical committee